CONTEXTUALIZING SANRO AUTHORITY THROUGH DEICTIC EXPRESSIONS IN BUGIS HEALING PRACTICES - Ramdayani, Sri; Mujaddidah, Husnul; Agus, Sitti Hasmah (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
This study explains how a Bugis sanro (traditional healer) constructs power through ritual speech in healing practices in Wajo, South Sulawesi. Employing a qualitative descriptive method, the researcher gathered data through direct observation, interviews, and audio-video recordings of the healing rituals. The analysis shows that the sanro’s authority is mainly built through two linguistic processes: contextualization and entextualization. First, contextualization is characterized by it- cleft construction and person deictic (first person, second person, third person, and first (inclusive)). Second, entextualization occurs when the sanro brings in Qur’anic verses, ancestral blessings, traditional Bugis mantras, and inherited ritual formulas. This entextualization occurs through the process of decontextualization and recontextualization. These texts, taken from older traditions and sacred sources, carry strong cultural and religious legitimacy. When the sanro inserts these texts into the healing moment, they strengthen her credibility and reinforce the belief that her words hold spiritual force. Together, these two processes show how ritual speech enables the sanro to gain trust, maintain authority, and perform effective healing.